The Impact of Accounting Systems on the Financial Performance: A Case Study of J&L Industries Limited Kampala - Asingura Shafigah (Uganda Christian University, 2024)
Worldwide, most switches have occurred in the community and working areas in the pressure on business subjects and in the requisite of owners, controllers, financial institutions, and other investors for adequate information provision, (Bader, 2018). These switches are shown also by the need to ensure different ways of using traditional methodizes for performance endurance. Therefore, highlighting a satisfactory performance level is the most basic significance towards the successful development of any organization, (Yaser, 2014). Provide an adequacy of high-quality information, reflecting the class of economic result and helping all the active bodies to understand the way performance is required, and the possibility of controlling the way they should design the existence of quality and complex information system and management control system, (Rainer, 2017). Under the terms of a corporate information system, an accounting subsystem is relevant in many cases, mostly concerning financial performance. Accounting is always related to making informed decisions on various subjects that will enable a company to invest its money wisely. In developed countries like the USA, Canada, China, and Japan, accounting system is conjoined with financial state and outcomes of firms. Economic performance is a composite of an organization concerning its financial health, ability, and willingness to meet its long-term financial obligations, and commitment to provide services in the future (Samer, 2016). According to Borhan, 2018, the output of AS primarily consists of financial reports, is needed at various levels of management and also by other users. Users need financial and related information with different degrees of detail and levels of analysis, (Hopwood, 2018). Innovative and state-of-the-art accounting practices that accompany computer-based AS are very difficult for most business owners to adopt in African countries. On the contrary, organizations are designing even more sophisticated accounting information systems to meet strategic goals and enhance performance (Eb, Pretorious, and Zuva, 2015). Common challenges that smaller firms, including SMEs face, especially in the developing countries in the adoption of computerized accounting system, include lack of capital and technological obsolescence, limited financial resources, management information, limited scale economies and management's IT-oriented behavior; and funds to improve the skills lack (Francalanci, 2017). The accounting information system is very instrumental to organizations in Uganda. They administer and collect information, which is usually ordinary or raw data, and its conversion into financial data for purposes of reporting to decision-makers (Affiliated, 2019). AS is a system that aids in the collection, recording, classification, and analysis of data and information on events that have an economic impact on organizations. It also helps in maintaining, processing, communicating of such information to the internal and external stakeholders respectively (Idan, 2020). Accounting systems generally help provide internal and external reporting data, financial statements and trend analysis capabilities affecting organizational performance.